Karakteristik Antioksidan Daun Pepe (Gymnema reticulatum Br.) Pada Berbagai Waktu Ekstraksi Dengan Metode Kombinasi Maserasi Dinamis dan Ultrasonikasi - Deva Jayadhi Narayana, Gede Agung Artha; Kadek Diah Puspawati, Gusti Ayu; Kartika Pratiwi, I Desak Putu (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Abstract Pepe leaf (Gymnema reticulatum Br.) is a creeping plant indigenous to India and Pakistan that typically grows in hedgerows and thickets. The leaves are traditionally consumed as an herbal beverage called